Post-transplant cyclophosphamide, calcineurin inhibitor, and mycophenolate mofetil compared to anti-thymocyte globulin, calcineurin inhibitor, and methotrexate combinations as graft-versus-host disease prophylaxis post allogeneic stem cell transplantation from sibling and unrelated donors in patients with acute myeloid leukemia: a study on behalf of the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation - Nagler, Arnon; Labopin, Myriam; Swoboda, Ryszard; Schroeder, Thomas; Hamladji, Rose-Marie; Griskevicius, Laimonas; Salmenniemi, Urpu; Rambaldi, Alessandro; Mielke, Stephan; Kulagin, Alexander; Passweg, Jakob R.; Luft, Thomas; et al. (Bone marrow transplantation, 2024)
Post-transplant cyclophosphamide plus calcineurin inhibitor (CNI)(tacrolimus or cyclosporine A) plus mycophenolate mofetil (PTCy/TAC or CSA/MMF) and anti-thymocyte globulin plus CNI (tacrolimus or cyclosporine A) plus methotrexate (ATG/TAC or CSA/MTX) are common graft-versus-host disease (GVHD) prophylaxis regimens. We compared the two regimens in patients with acute myeloid leukemia (AML) undergoing allogeneic transplantation from matched siblings or unrelated donors. 402 received PTCy/TAC or CSA/MMF and 5648 received ATG/TAC or CSA/MTX. Patients in the PTCy-based group were younger (48.7 vs. 51.5 years, p = 0.024) and there was a higher frequency of patient cytomegalovirus seropositivity and female donor to male patient combination in this group (77.8% vs. 71.8%, p = 0.009 and 18.4% vs. 14.4%, p = 0.029, respectively). More patients in the PTCy-based group received reduced-intensity conditioning (51.5% vs. 41%, p < 0.0001). No differences were observed in the incidence of acute GVHD grade II-IV and III-IV (21.2% vs. 20.4%, p = 0.92 and 8.1% vs. 6%, p = 0.1) or 2-year total and extensive chronic GVHD (33.7% vs. 30%, p = 0.09 and 10.7% vs. 11.2%, p = 0.81) between the groups. In the multivariate analysis, all transplant outcomes did not differ between the groups. PTCy/CNI/MMF and ATG/CNI/MTX are alternative regimens for GVHD prophylaxis in AML patients.
Online veröffentlicht am 13. April 2024
Gesehen am 24.09.2024